Beyond Technical Skills: The Integration of Language Competence into Professional Identity During International Teaching Practicum - Hidayati, Hidayati; Sulistiyo , Urip; Sartika, Delita; Habibi, Akhmad (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2025)
In the context of globalized teacher education, the integration of language competence into the development of professional identity among English as a Foreign Language (EFL) student-teachers remains insufficiently addressed. This study explores how non-native English-speaking student-teachers construct their professional identity through the lens of language competence during international teaching practicums. Employing a hermeneutic phenomenological approach, the research investigates the lived experiences of two Indonesian EFL student-teachers who participated in the Southeast Asian Ministers of Education Organization (SEAMEO) exchange program. Data collection involved semi-structured interviews and document analysis, including lesson plans, reflective journals, and mentor feedback. The analysis identified four key themes: language competence as a catalyst for identity formation, self-awareness as a foundation for professional growth, the integration of disciplinary knowledge into teaching practice, and student-centered engagement. The findings reveal divergent pathways in identity construction, shaped by how each participant perceived and responded to linguistic challenges. One student-teacher reframed language anxiety as an opportunity for transformation, while the other struggled with persistent self-doubt despite technical preparation. This study addresses a critical gap in teacher education literature by emphasizing how language competence functions as a core element of professional identity, rather than a supplementary skill. The results offer practical implications for designing teacher education curricula that prioritize reflective practice, language support, and identity development. By situating language competence within the broader process of becoming an effective educator, this study contributes to a more holistic understanding of teacher preparation in international and intercultural settings.